Yoga Practitioners Uniquely Activate the Superior Parietal Lobule and Supramarginal Gyrus During Emotion Regulation - Wadden, Katie P.; Snow, Nicholas J.; Sande, Peder; Slawson, Sian; Waller, Tom; Boyd, Lara A. (Frontiers in Integrative Neuroscience, 2018)
Emotion regulation is the process of monitoring and adjusting emotional responses to environmental stimuli and stressors. Evidence suggests that individuals who participate in physical activity are less likely to have an adverse response to a potentially stressful situation. The practice of yoga is a form of physical activity that may lessen individuals’ levels of stress and anxiety, and improve emotion regulation. Measuring heart rate variability (HRV) and brain activity using noninvasive functional magnetic resonance imaging (fMRI) provides a robust mechanistic approach to evaluating “neurovisceral” components of emotion regulation. The present study investigated the effects of yoga experience on the neurovisceral components (fMRI and HRV) of emotion regulation using a cross-sectional sample of yoga practitioners (YP) and physically active individuals without current yoga experience (recreational athletes; RA). Our primary aim was to determine whether YP participants exhibited different patterns of brain activation compared to RA participants, while viewing emotionally arousing visual stimuli. Our secondary aim was to examine potential differences across groups in HRV throughout the presentation of these stimuli. Inside a MR scanner, individuals watched film clips known to evoke emotions of happiness, sadness, or anger; these were counter-balanced by neutral video clips, intended to elicit no emotional response. When fMRI data were collapsed across all emotion-evoking conditions, the YP group activated two unique brain areas that included the superior parietal lobule and the supramarginal gyrus. These areas have been associated with attentional awareness and reduced egocentric bias, processes that have been implicated in emotion regulation by others. Concomitantly, the RA group activated the inferior middle frontal cortex, an area associated with cognitive reappraisal during emotion regulation. During viewing, the YP group demonstrated a trend towards a higher ratio of low- to high-frequency HRV compared to the RA group. The present study had a small sample size (RA: n = 12; YP: n = 19), which should be taken into account when interpreting the results. A larger sample is needed to determine the robustness of the present findings. The findings from this study support the presence of experience-dependent neurovisceral mechanisms associated with emotion regulation.